Math, asked by Anonymous, 1 year ago

using suitable identity, prove (0.87^3)+(0.13^3) /(0.87^2)+(0.87×0.13) +(0.13^2) =1

Answers

Answered by nikitasingh79
87
sign mistake in question it is (- (0.87×0.13))

(0.87^3)+(0.13^3) /(0.87^2)- (0.87×0.13) +(0.13^2) =1
[(a^3+b^3) = (a+b) (a^2+b^2-ab)]

= (0.87+0.13) (0.87^2+0.13^2-0.87×0.13) / (0.87^2)- (0.87×0.13) +(0.13^2)

= 0.87+ 0.13
= 1
Answered by anupamasahoo9696
2

Step-by-step explanation:

(a^3+b^3)/(a^2+b^2-ab)

a=0.87 b=0.13

=0.87+0.13

=1

Similar questions